The membrane attack complex as an indicator of complement hyperactivation in type 2 diabetes mellitus - Elina Alexandrovna Arakelova; Meri Robertovna Ovsepyan; Anna Surenovna Boyadzhyan; Arsen Artashesovich Arakelyan; Astkhik Artavazdovna Gevorkyan; Ashot Andreevich Mamikonyan (Сахарный диабет)
Aim. Comparative analysis of the levels of the membrane attack complex (MAC) - an end product of complement activation, and of hemolytic activitiesof C1 and C3 complement components in sera of patients with diabetes mellitus 2 (DM2) and healthy subjects. Materials and methods. 37 DM2 patients (7 men, 26 women, mean age 58?9 years (M?б) and 37 healthy subjects without a family history of hereditarydiabetes (17 men, 20 women, mean age 52?12 years). Serum MAC levels were measured by ELISA, C1 and C3 hemolytic activities by usingrabbit antibody-sensitized ram erythrocytes and C1, C3-deficient sera. Results. Mean values of all measured parameters in DM2 patients were significantly higher than in controls. Conclusion. Pathogenesis of DM2 is characterized by hyperactivation of the complement system including both the classical and terminal cascadesand by hyperproduction of its cytotoxic products.